Cryogenic electron ptychographic single particle analysis with wide bandwidth information transfer - Pei, X; Zhou, L; Huang, C; Boyce, M; Kim, J; Liberti, E; Hu, Y; Sasaki, T; Nellist, P; Zhang, P; Stuart, D; Kirkland, A; et al. (Springer Nature, 2023)
Advances in cryogenic transmission electron microscopy have revolutionised the determination of many macromolecular structures at atomic or near-atomic resolution. This method is based on conventional defocused phase contrast imaging. However, it has limitations of weaker contrast for small biological molecules embedded in vitreous ice, in comparison with cryo-ptychography, which shows increased contrast. Here we report a single-particle analysis based on the use of ptychographic reconstruction data, demonstrating that three dimensional reconstructions with a wide information transfer bandwidth can be recovered by Fourier domain synthesis. Our work suggests future applications in otherwise challenging single particle analyses, including small macromolecules and heterogeneous or flexible particles. In addition structure determination in situ within cells without the requirement for protein purification and expression may be possible.